PERAN PERGANTIAN MANAJEMEN, UKURAN PERUSAHAAN, DAN FINANCIAL DISTRESS TERHADAP AUDITOR SWITCHING (Media Riset Akuntansi, 2022)
The purpose of this study was to determine the effect of management turnover, firm size, and financial distress on auditor switching. The data used in this study is secondary data, in the form of audited reports of manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange for the period 2012-2016. Samples were obtained using purposive sampling method with a final number of 75 samples. This study uses logistic regression analysis as a hypothesis test with the application of the SPSS 23 program. The results show that management turnover has an effect on auditor switching, it is suspected because the company's management has the right to determine the KAP that will be used by the company. Meanwhile, company size and financial difficulties have no effect on auditor switching. The firm size variable has no effect, presumably because large companies have larger funds to finance audit fees. The financial distress variable has no effect, presumably due to unstable financial conditions to move to a new KAP.